Determination of antioxidant activities and total phenolic contents of three cyanobacterial species - Ali, H.E.A. (Trans Tech Publications Ltd, 2014)
The antioxidant activity and total phenolic content of different extracts (hexane, chloroform, ethyl acetate, ethanol (70) and water) of three tested cyanobacterial species (Phormidium sp., Oscillatoria sp. and Nostoc muscorum) were evaluated, using 2,2Â´-diphenyl-1-picrylhydrazyl (DPPH) scavenging method and FolinâCiocalteu method, respectively. The ethanolic extract of Oscillatoria sp. possessed the highest antioxidant activity (69.13Â±0.35) and therefore could be potential source of natural antioxidants. The correlation coefficients between the antioxidant activities and the phenolic contents were very small in most of extracts (R2 = 0.0291-0.2934). However, the water extract demonstrated relatively higher value (R2= 0.7446). Thus, phenolic compounds may not be considered the major contributors for the antioxidant activities of these cyanobacterial species. So, other antioxidant substances may be present in the extract and share in this activity. Â© 2014 Trans Tech Publications, Switzerland.